Suitability of NIID‐MDCK cells as a substrate for cell‐based influenza vaccine development from the perspective of adventitious virus susceptibility. (8th June 2022) - Hamamoto, Itsuki; Takahashi, Hitoshi; Shimasaki, Noriko; Nakamura, Kazuya; Mizuta, Katsumi; Sato, Ko; Nishimura, Hidekazu; Yamamoto, Norio; Hasegawa, Hideki; Odagiri, Takato; Tashiro, Masato; Nobusawa, Eri
Abstract: The practical use of cell‐based seasonal influenza vaccines is currently being considered in Japan. From the perspective of adventitious virus contamination, we assessed the suitability of NIID‐MDCK cells (NIID‐MDCK‐Cs) as a safe substrate for the isolation of influenza viruses from clinical specimens. We first established a sensitive multiplex real‐time PCR system to screen for 27 respiratory viruses and used it on 34 virus samples that were isolated by passaging influenza‐positive clinical specimens in NIID‐MDCK‐Cs. Incidentally, the limit of detection (LOD) of the system was 100 or fewer genome copies per reaction. In addition to influenza viruses, human enterovirus 68 (HEV‐D68) genomes were detected in two samples after two or three passages in NIID‐MDCK‐Cs. To further investigate the susceptibility of NIID‐MDCK‐Cs to adventitious viruses, eight common respiratory viruses were subjected to passages in NIID‐MDCK‐Cs. The genome copy numbers of seven viruses other than parainfluenza 3 decreased below the LOD by passage 4. By passaging in NIID‐MDCK‐Cs, the genome numbers of the input HEV‐D68, 1 × 10 8 copies, declined to 10 2 at passage 3 and to under the LOD at passage 4, whereas those of the other six viruses were under the LOD by passage 3. These results implied that during the process of isolating influenza viruses with NIID‐MDCK‐Cs, contaminating viruses other than parainfluenza 3 can be efficiently removed by passages in NIID‐MDCK‐Cs. NIID‐MDCK‐Cs could be a safe substrate for isolating influenza viruses that can be used to develop cell‐based influenza vaccine candidate viruses.